The bacterial flagellar rotary motor in action - Delalez, N; Armitage, J (Humana Press, 2018)
The bacterial flagellar motor is one of the few rotary motors in nature. Only ∼50 nm in diameter, this transmembrane, ion-driven nanomachine rotates a semirigid helical flagellum at speeds of up to 1300 rps. It is composed of at least 13 different proteins, in different copy numbers, resulting from the coordinated, sequential expression of more than 40 genes. Structural studies have revealed a great deal of information about the structure of the motor, but the in vivo activity has been more elusive. Using a multidisciplinary approach combining molecular biology with single molecule fluorescence microscopy and novel data analysis recent work has obtained quantitative data on the stoichiometry, dynamics, and turnover of components of functioning motors in vivo under physiological conditions. This has shown that it is not a stable rotary machine, but that its structure is highly dynamic and undergoes adaptive remodeling in response to different intracellular and extracellular signals.